Assessment of anxiety and depression among professional healthcare workers during the COVID-19 pandemic - observational cross-sectional study - Mohammed Mahmood Mohammed; Hayder Adnan Fawzi (Pensoft Publishers, 2024)
Aim: Evaluate the prevalence of depression among professional healthcare workers (PHCW) during the COVID-19 pandemic. Methods: A cross-sectional study was conducted during the fourth wave of COVID-19 infection in Iraq. A semi-structured questionnaire in English was used to obtain information about the study variables. Results: The study included 314 participants, with a mean age of 34.3 years, slightly higher male to female sex (55.1 to 44.9%), doctors represent (26.1%), pharmacist represent (26.4%) while 36.9% includes other PHCW (nurse, laboratory technician, doctor assistance, and paramedics). There was a high prevalence of depression in the current study (98.4%). There was no significant association between total HADS with sex, specialty, and duration of working in COVID-19 isolation wards. Meanwhile, age above 50 years appears to be associated with higher HADS scores compared to younger PHCW. Conclusion: Healthcare practitioners faced a heightened susceptibility to experiencing depression throughout the COVID-19 pandemic.